Manajemen Ketahanan Risiko Siber pada Internet of Things dan Cyber Physical System - Amalia Nurain; Rudy A.G. Gultom; Richardus Eko Indrajit (Journal on Education, 2024)
This research explores Cyber Risk Resilience Management on the Internet of Things (IoT) and Cyber Physical System (CPS). These two entities are closely linked to the internet, storing data about individuals or organizations. With cyberattacks on the rise, the impact can be direct, such as hardware damage, or indirect, such as reputation loss. The research aims to identify, assess, and manage cyber risks to maintain operational and system integrity. The literature study method was used to develop this approach. The results include how to identify attacks using the NIST framework with seven stages of incident recovery. This research provides a foundation for understanding and addressing cyber risks in IoT and CPS environments.